A novel floor-isolated re-centering system for prefabricated modular mass timber construction – Concept development and preliminary evaluation. (1st November 2020) - Chen, Zhiyong; Popovski, Marjan; Ni, Chun
Highlights: A seismic force resisting system FIRMOCS is proposed for the prefabricated modular timber construction. Specific finite element models were developed for analysing the seismic response of the proposed seismic system. With the proposed seismic system, the seismic performance of prefabricated modular mass timber construction was dramatically improved. Efficient and resilient prefabricated modular mass timber solution can be achieved with the proposed seismic system in high seismic zones. Abstract: Prefabricated modular mass timber (MT) construction provides a resource-efficient, consistent-quality, and eco-friendly solution for the building industry. Connections that facilitate the assembly of prefabricated modules to form the final structure usually do not possess the characteristics needed for performance of these systems in high seismic zones. In this study, a novel seismic force resisting system called FIRMOCS that incorporates floor-isolation and re-centering techniques, is proposed for the prefabricated modular MT construction. Finite element models of the Floor Isolated Re-entering Modular Construction System (FIRMOCS) and of regular modular construction Seismic Force Resisting Systems (SFRS) were developed in ABAQUS, a general-purpose finite element program. The seismic performance of the regular prefabricated modular MT SFRS and that of FIRMOC systems was evaluated using nonlinear dynamic time-history analysis along the principles of the National Building Code of Canada. The preliminary results showed that FIRMOC Systems significantly reduced the seismic demand on the prefabricated modular MT construction, thus leading to improved seismic response. Using the proposed novel SFRS, an efficient and resilient prefabricated modular MT construction solutions can be achieved in high seismic zones.